The Importance of Housing Organizations for The Development of Affordable Rental Housing - Daniela SPIRKOVA; Barbora BRESTOVSKA (Communications of International Proceedings, 2023)
Housing creates the conditions for exploiting the potential of the area as well as attracting skilled labour to the urban area, as well as improving the quality of life. Worldwide experience shows that the normal market environment does not allow addressing the housing needs of all population groups in a sufficiently flexible way. For this reason, national governments are seeking and applying various support instruments to increase the accessibility of housing for selected population groups as part of housing policy. It is also a matter of ensuring that the instruments used are effective and sustainable. It is through housing policy that the state creates the institutional environment needed to increase the accessibility of quality and healthy housing for a wide segment of the population. The aim of this article is to highlight the important function of housing corporations, which could be an important actor in the development of affordable housing also in the Slovak Republic.
Keywords: Housing and Rental Housing; Housing companies; Affordable housing